An efficient diazotroph‐derived nitrogen transfer pathway in coral reef system. Issue 4 (20th March 2023) - Sheng, Hua‐Xia; Wan, Xianhui S.; Zou, Bobo; Sun, Youfang; Hanoch, Buce; Zou, Wenbin; Yang, Weidi; Wu, Siqi; Huang, Hui; Ward, Bess B.; Kao, Shuh‐Ji
Abstract: The underlying mechanism for sustaining the high productivity of coral reefs in nutrient deplete water, known as the Darwin Paradox, has long been debated. The input of new nitrogen, for example, derived from N2 fixation, and efficient nitrogen recycling are hypothesized as two critical factors in resolving the paradox. However, the source of new nitrogen and its connection to nitrogen recycling in the coral reef system remain poorly understood. We measured N2 fixation rates and investigated the diazotroph community in different components of a tropical coral reef system. Our results show that the reef‐building crustose coralline algae demonstrate a significantly higher N2 fixation rate than the overlying water or the coral holobiont, representing a large source of N2 fixation to the system. The associated diazotroph community was dominated by the non‐cyanobacterial Rhizobiales . 15 N2 ‐based pulse‐chase incubation experiments revealed ~ 50% of the diazotroph‐derived nitrogen was released from the crustose coralline algae holobiont to the overlying water and coral holobiont within 48 h, which was five fold higher than the fraction of nitrogen released from nitrate‐based assimilation by crustose coralline algae. Furthermore, the released diazotroph‐derived nitrogen was rapidly transferred to the coral holobiont through grazing and was subsequently released back to the overlying water as dissolved organic nitrogen, revealing an efficient pathway that connects the new nitrogen input with the nitrogen recycling in the coral reef ecosystem. Our results provide new insights into the sources and fates of new nitrogen in the coral reefs, helping to resolve the Darwin Paradox in this unique ecosystem.